Diseño de un Sistema de Gestión de Seguridad y Salud en el Trabajo. Estudio de casos: Empresa Provincial de Conservas y Vegetales “LA CONCHITA”. Pinar del Río. Cuba. - Quintanilla Marín, Cristian Fernando (2012)
The system allows integrating postulates from the Strategic Address to the system study object, as well as its framing inside the System of Administration of Human resources and of the managerial strategy. The design and development of the SASST, allow to establish a planning, development and chronogram of activities on the integral administration for an appropriate appointment of responsibilities, use of resources, development of abilities, improving the dexterities in the workers and diminishing risks, tools and methods that allow to identify and to evaluate situations of danger and to minimize organizational losses surrendering. In the report the diagnosis is shown carried out in the company. When carrying out the diagnosis of the current situation of the administration of the Security and Occupational Health in the studied company you could appreciate the existence of deficiencies related with the first floor levels of the whole personnel's motivation for the Security and health in the work, the insufficient level of competitions (to know and to know how to make) of the human resources in this matter, the first floor level of the employees' participation in these activities, the insufficient level of elimination of insecure conditions, the lack of resources to confront the tasks of prevention of work accidents and professional illnesses.